2014
DOI: 10.1007/s00429-014-0912-8
|View full text |Cite
|
Sign up to set email alerts
|

The frontal aslant tract underlies speech fluency in persistent developmental stuttering

Abstract: The frontal aslant tract (FAT) is a pathway that connects the inferior frontal gyrus with the supplementary motor area (SMA) and pre-SMA. The FAT was recently identified and introduced as part of a "motor stream" that plays an important role in speech production. In this study, we use diffusion imaging to examine the hypothesis that the FAT underlies speech fluency, by studying its properties in individuals with persistent developmental stuttering, a speech disorder that disrupts the production of fluent speec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
127
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(147 citation statements)
references
References 82 publications
10
127
1
4
Order By: Relevance
“…Although little is known about the functional properties of the FAT, there is a growing interest in that novel tract [3,9,12,15,16,19,20]. The functional roles of FAT can be scrutinised to motor functions and language processing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although little is known about the functional properties of the FAT, there is a growing interest in that novel tract [3,9,12,15,16,19,20]. The functional roles of FAT can be scrutinised to motor functions and language processing.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms include the inability to produce grammatically correct and fluent speech with a preserved comprehension in most cases. On the other hand, damage to the pre-SMA causes a mild to severe speech impairment ranging from affected fluency to complete speech arrest (mutism) [10][11][12]20]. A recent study of patients suffering from primary progressive aphasia showed that pathological changes within the FAT affect verbal fluency with no influence on the overall language impairment, grammar deficits, repetition and single word comprehension [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolongation is one of the stuttering-like disfluencies described as the main clinical manifestation of the disorder [3][4][5]9,[17][18][19]29,30 . However, fluent people can also show prolongations in the speech flow, especially at the end of words 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Persistent Developmental Stuttering is a fluency disorder that affects about 1% of the adult population 1 characterized by disruptions in the speech flow that can be manifested through prolongations, blocks and repetitions [2][3][4][5] . These disfluencies are involuntary, occur at a higher frequency in relation to general population 6 and are considered the main characteristic of the disorder 7 .…”
Section: Introductionmentioning
confidence: 99%